Robert B. Parker's Killing the blues [compact disc, unabridged] - Brandman, Michael (Parker, Robert B., 1932-2010. Jesse Stone novels., 2011)
With summer just weeks away, Chief of Police Jesse Stone is pretty tense--and not just because Paradise, MA, is gearing up for the tourists. Stone finds himself dealing with car thefts, then murder, then someone who's come to town to remind him of his not-so-happy past as an L.A. cop. Fans mourning Parker's death will be happy to see that Brandman, who has written and produced numerous TV movies based on Parker's novels, has picked up where the best-selling author left off.